If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13.02=4.2(y-16.7)
We move all terms to the left:
13.02-(4.2(y-16.7))=0
We calculate terms in parentheses: -(4.2(y-16.7)), so:We get rid of parentheses
4.2(y-16.7)
We multiply parentheses
4.2y-70.14
Back to the equation:
-(4.2y-70.14)
-4.2y+70.14+13.02=0
We add all the numbers together, and all the variables
-4.2y+83.16=0
We move all terms containing y to the left, all other terms to the right
-4.2y=-83.16
y=-83.16/-4.2
y=19+2.4705882352941/3.0882352941176
| 2/5x+6=18 | | 4h-7+2=-9-5(-2h+10) | | 3n+11=71 | | 2x–11=13 | | .85x=20000 | | 2x–11=13 | | n+7=2n-18 | | 193.75t=15 | | -1/6v=-3 | | 10x+3=83 | | 2.4x=9.24 | | 0.5x-2.4=3.6 | | (3)/(8)y-5=(5)/(8)y-3 | | 3n=81-6n;n | | 23+4y+4y=9 | | -15-x=10 | | 1.4a=3 | | 3.1m-36.27=12.4 | | 3y+6=2y+38 | | 5/12=30/n | | 9+x/10=29 | | 36+7x=76-x | | (1.07)^(t/12)=2 | | 63=1/2(5x+7+8x-11) | | -1/2a+6=23 | | (1.07)^t/12=2 | | 3/4x+9=25 | | -15+3x+4=5x-14-7x | | 3.1(m-11.7)=12.4 | | 6+6(6)=y | | -15+3x+4=5x14-7x | | 3d-8-5=8 |